Finančné rozhodovanie vo finančnom manažmente - Bobáková, Viktória (Univerzita Pardubice, 2001)
The Slovak entrepreneurial sector face insufficiency of financial means, which are necessary for entrepreneurial activity. As the Slovak entreprises do not produce enough capital and reservers they depend on foreign ones. The foreign resources offer is influenced factors. Long-term foreign resources are inaccessible. A possible solution to this is to concentrate on increasing own capital and reserves.
Keywords: finance; finanční management; podnikatelské prostředí; banky